Depression among Medical Students of Quaid-e-Azam Medical College, Bahawalpur (Medical Forum Monthly, 2024)
Objective: Main purpose of this study was to see the Stress and depression in the medical students of Q.A.M.C, Bahawalpur.Study Design: Descriptive / cross-sectional study.Place and Duration of study: This study was conducted at the QAMC, Bahawalpur from 1st May 2016 to 1st August 2016.Materials and Methods: 150 both male and female students were included. Predesigned questionnaire was used to collect data. SPSS 20 Software used for data analysis and collected results were described in the form of frequencies tables, percentage and figures.Results: Seventy percent students were Non-depressed. Depression was more of the female gender. The number of depressed students was high in the 1st year followed by in 2nd year, the 3rd year, final year and 4th year. 13 % students were mildly depressed, 9% were moderately depressed and 8% students were severely depressed.Conclusion: The present study concludes that the depression rate is more among medical students.